RESEARCH OF INFLUENCE OF OXIDATION ON CONDITION OF THE BLANKS SURFACE FOR IMPROVEMENT OF QUALITY OF HOTROLLED SEAMLESS PIPES - I. A. Kovalyova; A. A. Kuchkov; A. V. Vengura; N. A. Hodosovskaya; I. A. Guzova; I. A. Ovchinnikova (Литьë и металлургия)
It is shown that research of scaling on the uninterruptedly-casted and the hot-rolled blanks, enabling to improve quality of production and due to that to increase its competitiveness, is actual